NUMERICAL SIMULATION OF THE GENERALIZED BURGER?S-HUXLEY EQUATION VIA TWO MESHLESS METHODS - Ahmad, Imtiaz; Abdel-khalek, Sayed; Alghamdi, Ahmed Mohammed; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
Numerical solution of the generalized Burger's-Huxley equation is established uti-lizing two effective meshless methods namely: local differential quadrature method and global method of line. Both the proposed meshless methods used radial basis functions to discretize space derivatives which convert the given model equation system of ODE and then we have utilized the Euler method to get the required numerical solution. Numerical experiments are carried out to check the efficiency and accuracy of the suggested meshless methods.
Keywords: meshless differential quadrature method; meshless method of line; radial basis function; generalized Burger?s-Huxley equation